Kashmir in India-Pakistan Relations: Perspective Pakistan’s Nuclear Policy, Background and Development Towards Conflict Resolution - Taimor Khurshad (GoAcademica Research & Publishing, 2020)
The conflict between India and Pakistan over the Kashmir problem still seems to be an obstacle in their relations. It has been 58 years since the dispute has passed, but there is no final agreement that can be accepted by both parties. If 1947 is the day of independence for India and Pakistan, then that year is the beginning of the suffering of the people of Kashmir. Pakistan as the party that has the right to make Kashmir as part of its territory feels the need to continue to raise this issue even though it has to develop nuclear though.